BAURAN PEMASARAN DAN STRATEGI PENGEMBANGAN SUSU KAMBING (STUDI KASUS PADA KARYA ETAWA FARM BANYUWANGI) - Ton, Sefri; Rahayu, Ninik Sri; Slamet, Risky (Lampung University, 2024)
The purpose of this study was to analyze the marketing mix and development strategy of goat milk at Karya Etawa Farm, Kalipuro District, Banyuwangi Regency. The research method is a case study using descriptive analysis data and SWOT analysis. Data were collected in April - July 2021. The results of the study showed that the marketing mix in Karya Etawa Farm includes (a) goat milk products produced have various flavors and good quality, (b) product prices follow competitors, (c) milk distribution is carried out either directly to consumers or through retailers, (d) promotional activities are carried out through face-to-face and sales promotions. The business development strategy can be carried out through (a) business owners utilizing and maintaining business locations to produce quality products and improve marketing networks, b) maintaining product quality by utilizing support and supervision from the government, (c) maintaining product quality and setting competitive market prices, (d) strengthening and expanding marketing network cooperation through resellers of goat milk products, (e) using more modern technology to produce quality products and raise interest in goat milk consumption. Keywords: marketing mix, goat milk, development strategies